Sea-ice derived meltwater stratification slows the biological carbon pump: results from continuous observations - von Appen, Wilken-Jon; Waite, Anya M.; Bergmann, Melanie; Bienhold, Christina; Boebel, Olaf; Bracher, Astrid; Cisewski, Boris; Hagemann, Jonas; Hoppema, Mario; Iversen, Morten H.; Konrad, Christian; Krumpen, Thomas; et al. (Nature communications, 2021)
The ocean moderates the world’s climate through absorption of heat and carbon, but how much carbon the ocean will continue to absorb remains unknown. The North Atlantic Ocean west (Baffin Bay/Labrador Sea) and east (Fram Strait/Greenland Sea) of Greenland features the most intense absorption of anthropogenic carbon globally; the biological carbon pump (BCP) contributes substantially. As Arctic sea-ice melts, the BCP changes, impacting global climate and other critical ocean attributes (e.g. biodiversity). Full understanding requires year-round observations across a range of ice conditions. Here we present such observations: autonomously collected Eulerian continuous 24-month time-series in Fram Strait. We show that, compared to ice-unaffected conditions, sea-ice derived meltwater stratification slows the BCP by 4 months, a shift from an export to a retention system, with measurable impacts on benthic communities. This has implications for ecosystem dynamics in the future warmer Arctic where the seasonal ice zone is expected to expand. The North Atlantic biological pump has the most intense absorption of C globally, but how this will fare in light of climate changes (especially sea-ice melting) is poorly understood. Here the authors present a 24-month continuous time series of physical, chemical, and biological observations in the Fram Strait.